The Impact of Transformational Leadership and Readiness for Change on Employee Performance at the Higher Education Service Institution Region II Palembang - Maulana, Rizki Dimas; Kurniawan, Mohammad; Lazuarni, Shafiera (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study aims to examine the influence of transformational leadership and readiness for change on employee performance at LLDIKTI Region II during the ongoing digital transformation process. A quantitative approach was employed, with data collected through questionnaires distributed to 60 respondents. The data were analyzed using multiple linear regression with the help of SPSS version 27. The results indicate that both transformational leadership and readiness for change have a positive and significant impact on employee performance, both partially and simultaneously. The t-test results show that both variables are statistically significant (t-value of 3.667 for transformational leadership and 2.838 for readiness for change), with a significance level below 0.05. The F-test result shows an F-value of 22.487, which is greater than the F-table value of 3.15, with a significance level of 0.000. The R² value of 0.441 indicates that these two variables explain 44.1% of the variance in employee performance.These findings carry practical implications for LLDIKTI Region II, particularly in supporting digital transformation. It is recommended that LLDIKTI develop leadership training and mentoring programs to promote the consistent application of transformational leadership principles. Moreover, the organization should enhance employee readiness for change by providing technological training, clear change communication, and reward systems. This approach will help the institution improve adaptability and support optimal employee performance in the digital era.